Pengaruh Pemberian Aromaterapi Lemon terhadap Skor Kecemasan Mahasiswi Fakultas Kedokteran Universitas Diponegoro - Fitrikasari, Alifiati; Fajriyanti, Nur Isnaeni; Wardani, Natalia Dewi; Jusup, Innawati (RSUP Dr. Kariadi, 2020)
Background: Based by Riskesdas in 2013, 6% of Indonesia’s population the age of 15 years old and more had emotional disorders which shown by symptoms of anxiety and depression. In university students, the study found that 25% of them had light anxiety, 60% had moderate anxiety, and 15% had severe anxiety. The mean of medical student who had anxiety symptoms around the world are 12-69%. Relaxation therapy able to decrease anxiety level, which by giving aromatherapy, it able to stimulates the brain to relax. Lemon is one of the aromatherapies that found effectively able to decrease anxiety symptoms by its refreshingly sharp smell and lifting the mood, which strengthening its user’s psyche. To measure the anxiety score, the author used the Zung Self-rating Anxiety Scale (ZSAS). The objective of this study aimed to investigate the effect of inhaling lemon aromatherapy on anxiety in female students of Medical Faculty of Diponegoro University Methods: This study used experimental pre and post-test without control design. Zung Self-rating Anxiety Scale was used to investigate the anxiety level of the samples. 32 persons volunteered as participants by 1 of them dropped out. The group inhaled lemon aromatherapy for 2 weeks. At the end of week 2, the participants’ anxiety was measured, and the results were statistically analysed. Saphiro-Wilk Test was used as the normality test while the results of the measured anxiety were tested by Wilcoxon Test. Results: There was a significant decreased anxiety score of the participants after inhaling lemon aromatherapy for two weeks. Based by pre and post-test result, the mean of anxiety score decreased from 37.32 to 31.84 (p=0.000). Conclusions: Lemon aromatherapy essential oil is able to significantly decrease the anxiety score of female students of Faculty of Medicine Diponegoro University. Keywords: Lemon aromatherapy, anxiety, medical student